Overactive performance monitoring in obsessive–compulsive disorder is independent of symptom expression - Riesel, Anja; Kathmann, Norbert; Endrass, Tanja (European archives of psychiatry and clinical neuroscience, 2014)
Overactive performance monitoring has been consistently reported in obsessive–compulsive disorder (OCD). OCD is a clinically heterogeneous disorder and is characterized by several symptom dimensions that may have partially distinct neural correlates. We examined whether performance-monitoring alterations are related to symptom severity and symptom dimensions. Electrocortical correlates of performance monitoring were assessed in 72 OCD patients and 72 matched healthy comparison participants during a flanker task. Amplitudes of the error- and correct-related negativity as well as delta and theta power were used to quantify performance-monitoring activity, and a composite measure was derived using factor analysis. Symptom dimension scores were obtained from the Yale-Brown Obsessive Compulsive Scale symptom checklist. OCD patients showed increased electrocortical responses associated with correct and erroneous responses compared to healthy comparison participants. In patients, no correlations were obtained between performance monitoring and global symptom severity as well as lifetime symptom dimension scores. Only a statistical trend was found that higher symmetry/hoarding scores were associated with reduced performance-monitoring activity. For present symptom dimensions scores, an association with rituals/superstitious symptoms was obtained such that higher scores were associated with greater performance-monitoring activity. However, for both dimensions, subjects with low scores or high scores on each dimension were characterized by overactive performance monitoring compared to healthy controls. Overactive brain processes during performance monitoring are a neural correlate of OCD that is independent of global symptom severity and can be observed for all symptom dimensions. This supports the notion of overactive performance monitoring being a candidate endophenotype for OCD.